An Investigatory Project of Zingiber officinale (Ginger) Ointment as an Alternative Remedy for Headache and Nasal Congestion: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Now, ointment/vapour rub is used almost whenever someone feels a headache or nasal congestion. We research natural ointment/commercial ointment that can have a toxic effect on your health. The construction of ginger as an ointment/vapour rub can benefit those who have suffered from headaches and nasal congestion. This study aims to determine ginger’s effectiveness for those suffering from headaches and nasal congestion and to be less expensive so everyone can afford it.  The research design used for the study was quantitative experimental research while utilizing a purposive sampling technique. The statistical used for this study was an F-test to determine the difference between the two groups of respondents. They use a questionnaire as the research instrument, the model in terms of construction material, design, effectiveness, and presentation. The study's respondents comprise 4 STEM Students and 3 STEM teachers. The following procedures were undertaken to conduct the ginger as an ointment/vapour rub: The material will be first cleaned and prepped. The ginger must then be carefully washed, grated, and extracted. To eliminate contaminants and ginger pulp, the ginger extract will be filtered. The pan will be heated before combining the petroleum jelly, essence oil, and olive oil. The ginger extract will be gradually added after the jelly and olive have been mixed, and the mixture must be stored until all of the components have been combined. The mixture must then be taken from the fire and stirred until it has cooled. After cooling, the mixture will be packed into the sanitized bottle and stored in a cool, dry location. The study results regarding construction materials, design, and presentation are strongly agreed upon. The overall mean of STEM Students was 4.42, interpreted as moderately agree, and STEM Teachers have an overall mean of 4.97, interpreted as strongly agree. The F-value was 2.2276, and the F-computed was 0.807. It indicates no significant difference between the assessment of the two groups of respondents. To further improve the study, the respondents recommend adding menthol to the ingredients and changing the colour to improve the model.
Keywords: Alternative Remedy; Ginger